Effects of Gibberellic Acid (Ga3) on Growth and Yield Parameters of French Bean (Phaseolus Vulgaris L.) (Journal of the Asiatic Society of Bangladesh, Science, 2017)
A field study was conducted during the Rabi season of 2009-2010 in the research field of Bangladesh Council of Scientific and Industrial Research (BCSIR), Dhaka. Six levels of GA3, viz. 0, 30, 50, 70, 90 and 110 ppm were sprayed at 18 days after sowing (DAS). GA3 treatments significantly increased plant height than the control plants. GA3 with 30 to 90 ppm significantly increased number of branches and leaves, leaf area, leaf area index (LAI), leaf dry matter and total dry matter at different growth stages. GA3 at 30 to 70 ppm gradually increased crop growth rate (CGR), net assimilation rate (NAR) and relative growth rate (RGR) and declined advanced growth stages. Number of dry pods /plant, number of seeds /pod, 1000 seed weight, fresh fodder, fresh pod, dry seed yield and harvest index also significantly increased. Positive significant correlations were found among growth parameters and as well as yield contributing characters.Asiat. Soc. Bangladesh, Sci. 43(1): 49-60, June 2017